Maternal Age, Parity, Body Mass Index, and Hypertension History Associated with Preeclampsia - Lenny Stia Pusporini; Non Arofani Zakiyatunnisa; Delly Arfa Syukrowardi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Preeclampsia remains a major contributor to maternal and perinatal morbidity and mortality. This study examined associations of maternal age, parity, body mass index (BMI), and a history of hypertension with preeclampsia at Kartini Hospital, Rangkasbitung, Indonesia. An unmatched case-control study used medical records from January–December 2025. The sample comprised 216 women who delivered at the hospital: 108 preeclampsia cases selected by total sampling and 108 non-preeclampsia controls selected purposively. Categorical associations were tested using Pearson's chi-square test, with odds ratios (ORs) and 95% confidence intervals (CIs) derived from 2×2 tables. High-risk maternal age (<20 or >35 years) was associated with preeclampsia (OR 4.28, 95% CI 2.25–8.14; p<0.001), as were parity (OR 0.32 for primigravida versus multigravida, 95% CI 0.18–0.58; p<0.001) and obesity (BMI ≥30 kg/m²; OR 8.45, 95% CI 2.44–29.27; p<0.001). All nine women with a hypertension history were cases (p=0.002), precluding an uncorrected OR estimate. Maternal risk screening should begin during preconception and antenatal care, with particular attention to age, obesity, obstetric history, and chronic hypertension.